Study on Experiment Platform of Integrated Steering and Braking Control for Vehicle Active Safety System - Tong Liang; Zhang Beibei (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
An experiment platform which aims to study the integration control of steering and braking is designed due to the research requirement of vehicle active safety control strategy. A test vehicle which is equipped with the systems of steer-by-wire and brake-by-wire is provided and the Autobox, combined with Matlab/simulink and MSCCarsim,is used to fulfill the RCP(Rapid Control Prototyping) and HIL(Hardware-in-loop). The seven-freedom vehicle model is constructed first and the approach of vehicle parameters estimation based on the Extended Kalman Filter is proposed. The primary control methods and controller designment is carried out to prove the validation of the platform.